2016
DOI: 10.1038/srep26070
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Fluidized Bed Bioartificial Liver in Treating Fulminant Hepatic Failure in Pigs: A Metabolomics Study

Abstract: Bioartificial livers may act as a promising therapy for fulminant hepatic failure (FHF) with better accessibility and less injury compared to orthotopic liver transplantation. This study aims to evaluate the efficacy and safety of a fluidized bed bioartificial liver (FBBAL) and to explore its therapeutic mechanisms based on metabolomics. FHF was induced by D-galactosamine. Eighteen hours later, pigs were treated with an FBBAL containing encapsulated primary porcine hepatocytes (B group), with a sham FBBAL (con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Our findings are in line with previous studies that demonstrated diminished levels of serum phospholipid metabolites in patients with liver diseases (including HCC, liver cirrhosis, hepatitis, and liver failure)[ 7 , 9 ]. Indeed, through an untargeted metabolomics approach, we found significantly reduced amounts of phospholipid metabolites in patients with HCC.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are in line with previous studies that demonstrated diminished levels of serum phospholipid metabolites in patients with liver diseases (including HCC, liver cirrhosis, hepatitis, and liver failure)[ 7 , 9 ]. Indeed, through an untargeted metabolomics approach, we found significantly reduced amounts of phospholipid metabolites in patients with HCC.…”
Section: Discussionsupporting
confidence: 93%
“…There were no statistical differences in age and sex among the patients with HCC, patients with cirrhosis, and healthy controls. Also, the constituent ratio of etiology of liver injury (pathogenesis) was comparable between the HCC and cirrhosis groups, all of which confirm the reliability of the UPLC-MS assay and optimal homogeneity of baseline characteristics[ 9 ].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Currently, D-gal is usually administered through the external jugular vein or the abdominal cavity[ 23 - 25 , 27 ]. The abdominal cavity injection is simple and convenient, but resulting models are unstable, while administration through the external jugular vein and portal vein usually requires a long anesthesia time and surgical venous intubation, so the method is more complicated.…”
Section: Discussionmentioning
confidence: 99%
“…Further, in a study using porcine hepatocytes in a fluidised bed bioreactor in pigs with liver failure, whilst survival time in a D-galactosamine model was increased, there were marked perturbations in the serum metabolome, e.g. reductions in some phospholipids in particular phosphatidyl and lysophosphatidyl cholines as well as fatty acids 24 , molecules intimately associated with the stress response. It is also known that primary porcine hepatocytes are prone to loss of function and apoptosis in vitro 25 .…”
Section: Discussionmentioning
confidence: 99%